2016
DOI: 10.1530/erp-16-0018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mitral geometry and global afterload on improvement of mitral regurgitation after trans-catheter aortic valve implantation

Abstract: ObjectiveTo assess the impact of mitral geometry, left ventricular (LV) remodelling and global LV afterload on mitral regurgitation (MR) after trans-catheter aortic valve implantation (TAVI).MethodsIn this study, 60 patients who underwent TAVI were evaluated by 3D echocardiography at baseline, 1 month and 6 months after procedure. The proportional change in MR following TAVI was determined by examining the percentage change in vena contracta (VC) at 6 months. Patients having a significant reduction of at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
(14 reference statements)
2
5
0
1
Order By: Relevance
“…We conducted detailed analyses of MR Several investigators reported that the frequency of improvement in preexisting MR after TAVR was 30%−50%. [1][2][3][4][5][6][7][8][9] Our study was concordant with those studies but exhibited one of the highest rates of MR improvement. Probably, this high recovery rate of MR may be related to the afterload dependency of MR volume at the baseline in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We conducted detailed analyses of MR Several investigators reported that the frequency of improvement in preexisting MR after TAVR was 30%−50%. [1][2][3][4][5][6][7][8][9] Our study was concordant with those studies but exhibited one of the highest rates of MR improvement. Probably, this high recovery rate of MR may be related to the afterload dependency of MR volume at the baseline in this study.…”
Section: Discussionsupporting
confidence: 91%
“…19 We calculated the Zva = (SAP + MG)/stroke volume index, where SAP is the systolic arterial pressure and MG is the mean transvalvular pressure gradient, as previously described. 7 ESWS contains a component of LV geometrical adaptation to the afterload, which Zva does not have. The Chi-squared test was used for categorical variables.…”
Section: Methodsmentioning
confidence: 99%
“…Both mentioned components of functional MR led to mitral apparatus geometry deformation, including leaflet restriction, enlargement of the mitral ring, and increase in distance between papillary muscles. Considering the complexity of the MR pathomechanism in patients with AS and improvement of left ventricular function after TAVI, a reduction in the significance of MR after the procedure should be expected [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…also showed the importance of mitral annulus diameter and area reduction (2D and 3D analysis) in the group with MR improvement. Moreover, they observed no effect of TAVI on MR in the group with restriction of mitral leaflets, which is a consequence of mitral complex geometry change, as the greater distance between papillary muscles [ 16 ]. In our study, a significant decrease of sPAP was observed, although it may be the result of aortic valve implantation as well as a decrease in the significance of MR.…”
Section: Discussionmentioning
confidence: 99%
“…Επιπλέον, άλλες μελέτες αναφέρουν ότι επιπλοκές όπως η εμφύτευση μόνιμου βηματοδότη συνεπεία πλήρους κολποκοιλιακού αποκλεισμού 123 και ο υψηλός βαθμός παραβαλβιδικής διαφυγής 124 αποτελούν σημαντικούς προγνωστικούς παράγοντες ελαττωμένου ΚΕΑΚ μετεπεμβατικά.Σχετικά με τα δημογραφικά χαρακτηριστικά της παρούσας μελέτης, η μέση ηλικία των ασθενών του δείγματός μας (81,8 έτη) φάνηκε πως είναι απολύτως συγκρίσιμη με πολλές μελέτες από την υπάρχουσα βιβλιογραφία 99,107,[125][126][127]. Τέλος, οι γυναίκες αποτέλεσαν την πλειοψηφία του δείγματος (56%) εύρημα που βρίσκεται σε συμφωνία με τα υπάρχοντα βιβλιογραφικά δεδομένα,99,105,106,127,128 με ελάχιστες εξαιρέσεις,112,129,130 όπου η αναλογία των ανδρών είναι μεγαλύτερη εκείνης των γυναικών. TAVI μέσω της διαμηριαίας οδού 58.…”
unclassified